Membangun Komunitas Desa Bersih Melalui Sanitasi Total Berbasis Masyarakat (STBM) untuk Mengurangi Penyebaran Penyakit di Desa Berembang - Sari, Fiqi Nurmanda; Nurfadliyati, Nurfadliyati; Gunawan, Hendra; Huda, Imam Arifa’illah Syaiful; Harianto, Dodi (Abdimas Universal, 2025)
Berembang Village, Muara Jambi District, exhibits vulnerability to disease spread due to substandard sanitation. The prevalent use of latrines, constructed and utilized extensively by the local community, particularly by residents near the Batanghari River, highlights this issue. Based on situational analysis, this community service aims to enhance awareness and availability of sanitation, specifically adequate latrines or toilets, and to develop a policy for Community-Based Total Sanitation (CBTS). To achieve these objectives, several strategies are employed: awareness campaigns about proper sanitation, provision of squat toilets to the less fortunate, and support in policy-making for sanitation program implementation. The outcomes of this community service include: (1) improved understanding of clean living practices through awareness campaigns, (2) distribution of seated toilets to the needy who lack such facilities, and; (3) drafting policies for the implementation of sanitation programs. Through this community service, it is hoped that the residents of Berembang Village will experience improvements in, and maintenance of, sanitation, and serve as a role model for other villages in addressing sanitation and public health challenges.